POSTERIOR PRECORTICAL VITREOUS POCKETS IN HIGH MYOPIA OBSERVED BY ENHANCED VITREOUS IMAGING OF SPECTRAL DOMAIN OPTICAL COHERENCE TOMOGRAPHY. Issue 6 (June 2019) - Wang, Xiaohan; Shen, Mengxi; Wang, Ruoshi; Zhou, Yanping; Li, Tong; Xiao, Meichun; Song, Minlu; Sun, Xiaodong; Wang, Fenghua
Abstract : Purpose: To observe the vitreous in highly myopic eyes with posterior precortical vitreous pockets (PPVPs) using enhanced vitreous imaging of spectral domain optical coherence tomography. Methods: Fifty-two highly myopic eyes with PPVPs of 36 patients were included in this study. All subjects underwent enhanced vitreous imaging optical coherence tomography. The size of PPVPs was measured, and the frequency of imaging features was recorded. Results: Nine imaging features of the vitreous in highly myopic eyes with PPVPs were found. The average age of subjects was 38.1 ± 10.8 years. The mean height of PPVPs was 1, 177 ± 704 μ m, and the mean width was 7, 440 ± 755 μ m. Hyperreflective line and the interlayer were observed in 30 (57.7%) eyes. Hyperreflective dots were found in 37 (71.2%) eyes. More central vitreous space was more frequently detected in younger patients. Prevascular vitreous fissure was detected in 7 (13.5%) eyes. W-shaped cavity, identified as an empty space with a smooth W-shaped edge, was demonstrated to be the fusion of Cloquet's canal and the extension of PPVPs. Perpendicular hyperreflective parallel strands were detected in 3 (5.8%) eyes. Hyperreflective network was observed in 10 (19.2%) eyes. Hyperreflective parapapillary tubercle was found in 7 (13.5%) eyes. Conclusion: Nine imaging features of the vitreous in highly myopic eyes with PPVPs were visualized by enhanced vitreous imaging optical coherence tomography. Abstract : Nine imaging features of the vitreous in highly myopic eyes with posterior precortical vitreous pockets were visualized using enhanced vitreous imaging of spectral domain optical coherence tomography. The authors' observations may have implications in the pathogenesis of early vitreous change in high myopia.